Specific and Efficient Uptake of Surfactant-Free Poly(Lactic Acid) Nanovaccine Vehicles by Mucosal Dendritic Cells in Adult Zebrafish after Bath Immersion - Rességuier, Julien; Delaune, Emilie; Coolen, Anne-Line; Levraud, Jean-Pierre; Boudinot, Pierre; Le Guellec, Dominique; Verrier, Bernard (Frontiers in Immunology, 2017)
Activation of mucosal immunity is a key milestone for next-generation vaccine development. Biocompatible polymer-based nanoparticles are promising vectors and adjuvants for mucosal vaccination. However, their in vivo uptake by mucosae and their biodistribution in antigen-presenting cells need to be better understood to optimize mucosal nanovaccine designs. Here, we assessed if antigen-presenting cells are efficiently targeted in a spontaneous manner by surfactant-free poly(lactic acid) nanoparticles (PLA-NPs) after mucosal administration. Combining histology and flow imaging approaches, we describe and quantify the mucosal uptake of 200nm PLA-NPs in adult zebrafish. Following bath administration, PLA-NPs penetrated and crossed epithelial barriers from all exposed mucosae. In mucosae, PLA-NPs accumulated in antigen-presenting cells, which were identified as dendritic cells, macrophages and IgZ+ B cells in gills and skin. PLA-NP uptake by phagocytes was specific to these cell types, as PLA-NPs were not detected in neutrophils. Importantly, quantitative analyses in gills revealed that dendritic cells take up PLA-NPs with specifically high efficiency. This study shows that surfactant-free PLA-NPs, which display optimal biocompatibility, can spontaneously target dendritic cells with high efficiency in vivo following mucosal administration, and highlights PLA-NPs as powerful platforms for mucosal vaccine delivery in the medical and veterinary fields, and particularly in aquaculture.